Impact of anthropogenic landscape transformation on soil fertility and diversity of carabid beetles and butterflies in Poland - Katarzyna Szyszko-Podgórska; Joanna Ukalska; Krzysztof Ukalski; Marek Kondras (Global Ecology and Conservation, 2025)
Anthropogenic landscape transformation, including urbanization and intensive agriculture, significantly affects the structure and functioning of ecosystems. The result of these changes is the disruption of species population dynamics and a decline in biodiversity. Understanding the impact of soil characteristics on biodiversity is crucial to landscape ecology, particularly in the context of indicator species such as butterflies and Carabid beetles. The present study aimed to investigate the influence of soil variables on the occurrence and diversity of butterflies and Carabid beetles in three regions of Poland. In addition, the study sought to determine how the history of land use affects the current soil properties and community structure of the organisms in different types of ecosystems. The results showed significant differences in soil variables depending on land use form. High HSI (habitat soil index) values in soils from agricultural land indicate that historical agrarian use, and thus the application of fertilizers, have influenced their fertility. High butterfly diversity was associated with rich open land soils, while beetle diversity was less dependent on soil fertility and more resistant to environmental changes. The RDA method showed that K, Ca, Mg, and N are key soil variables affecting butterfly diversity, while in beetles, K, Mg, and HSI are key soil variables affecting diversity. The study underscores the need to consider land use history in soil management to promote biodiversity. The results suggest that a diverse approach to environmental management, tailored to local conditions, can increase the effectiveness of biodiversity conservation. Management strategies should focus on maintaining habitat diversity, which is key to maintaining healthy ecosystems.